Nervus Trigeminus: Structure, Functions, and Clinical Significance - Nafosat Yunusova (Scientific Trends, 2024)
The trigeminal nerve (Nervus Trigeminus) is one of the largest and most important cranial nerves, responsible for transmitting sensory information from the face and head to the central nervous system and controlling the muscles involved in mastication. Its three main branches (ophthalmic, maxillary, and mandibular) innervate various anatomical structures, enhancing its functional importance.